PE Metrics : assessing student performance using the national standards & grade-level outcomes for K-12 physical education - Chepko, Stevie; Holt/Hale, Shirley Ann; Doan, Robert John; MacDonald, Lynn Couturier, 1959-; SHAPE America (Organization). (Reston, VA : SHAPE America, Society of Health and Physical Educators ; Champaign, IL : Human Kinetics, 2018)
'Provides assessments that measure student achievement of SHAPE America's Grade-Level Outcomes and thus serves as a companion book for the Standards book and the three SHAPE America Lesson Planning books. Scope--covers most of the elementary grade-level outcomes and samples for middle school and high school plus info on how to create more assessments. Written for K-12 physical education teachers, K-12 physical education administrators and curriculum writers, and PETE students'--
Assessment for the 21st century -- Sample assessments for elementary school physical education -- Sample assessments for middle school physical education -- Sample assessments for high school physical education.
This book is a revised edition of PE Metrics: assessing national standards 1-6 in elementary school, published in 2010 and 2011 by National Association for Sport and Physical Education.
Includes bibliographical references.
Keywords: Physical education for children -- Study and teaching -- United States; Physical education for children -- United States -- Evaluation; Physical education for children -- Curricula -- United States; Physical education for children -- Standards -- United States